2018
DOI: 10.1002/oby.22298
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle miRNAs as Biomarkers of Vascular Function and Inflammation Response to Aerobic Exercise in Obesity?

Abstract: Objective This study aimed to explore the role of nine microRNAs (miRNAs) in microparticles (MPs) on the efficacy of aerobic exercise in the regulation of inflammation and vascular function in obesity. Methods Sedentary women with normal weight (n = 6, BMI < 25 kg/m2) and women with obesity (n = 9, BMI > 30 kg/m2) were recruited at F. Hached Hospital (Sousse, Tunisia) and enrolled in an 8‐week aerobic program. Vascular function was assessed using laser Doppler flowmetry/iontophoresis, circulating MPs by flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
(56 reference statements)
0
28
0
Order By: Relevance
“…In exercise, the expression of various members of this family was reported to increase after a marathon or systematic training with walking/running in middle-aged men and women [ 118 , 129 ] or decrease in acute and systematic cycling training in middle-aged participants [ 123 , 128 ]. miR-21 may have both pro- and anti-inflammatory properties, and its expression is reported to be rising in participants of marathons and some studies with acute cycling and sustained rowing exercise and high-intensity intervals or endurance training [ 117 , 124 , 125 , 127 , 130 , 133 ]. On the other hand, there was a study on acute cycling by athletes (basketball players) where the miR-21 expression was decreased [ 126 ].…”
Section: Epigenetic Changes Involved In Immune Responsesmentioning
confidence: 99%
“…In exercise, the expression of various members of this family was reported to increase after a marathon or systematic training with walking/running in middle-aged men and women [ 118 , 129 ] or decrease in acute and systematic cycling training in middle-aged participants [ 123 , 128 ]. miR-21 may have both pro- and anti-inflammatory properties, and its expression is reported to be rising in participants of marathons and some studies with acute cycling and sustained rowing exercise and high-intensity intervals or endurance training [ 117 , 124 , 125 , 127 , 130 , 133 ]. On the other hand, there was a study on acute cycling by athletes (basketball players) where the miR-21 expression was decreased [ 126 ].…”
Section: Epigenetic Changes Involved In Immune Responsesmentioning
confidence: 99%
“…A great number of studies have shown that miRNAs are differently enriched in MVs, and their expression patterns also change with respect to different diseases . Therefore, MVs and associated miRNAs are considered to be potential diagnostic biomarkers of diseases . For instance, in a prospective study, in 176 patients with stable coronary artery disease (CAD), Jansen F at al.…”
Section: Existing Problems Of Mvs and The Clinical Prospectsmentioning
confidence: 99%
“…130 Therefore, MVs and associated miRNAs are considered to be potential diagnostic biomarkers of diseases. [131][132][133] For instance, in a prospective study, in 176 patients with stable coronary artery disease (CAD), Jansen F at al. found that the level of miR-126 or miR-199a expression in circulating MVs but not in plasma could predict the occurrence of cardiovascular events in stable CAD patients.…”
Section: The Clinical Prospect Of Mvsmentioning
confidence: 99%
“…miR-129-5p isolated from plasma MVs was demonstrated to be a sensitive and specific biomarker for heart failure (HF) in univentricular heart disease [ 17 ]. In addition, MP miR-124a and miR-150, which were found to be more abundant in obese subjects compared to normal weight controls, were found to be significantly associated with inflammation and vascular function in obesity [ 18 ]. As a consequence, lEV-miRNAs are emerging as attractive biomarkers due to their stability and easy detection in biofluids.…”
Section: Introductionmentioning
confidence: 99%